Antiviral activity of interferon‐stimulated gene 20, as a putative repressor binding to hepatitis B virus enhancer II and core promoter - Park, Yong Kwang (J Gastroenterol Hepatol, 2020)
BACKGROUND AND AIM: Interferon‐stimulated gene 20 (ISG20) is an interferon‐inducible exonuclease that inhibits the replication of several RNA viruses. In patients with chronic hepatitis B, ISG20 expression is related to the interferon‐α treatment response. However, the molecular mechanism of ISG20‐mediated anti‐hepatitis B virus (HBV) activity is unclear. METHODS: We have investigated the effect of ISG20 on antiviral activity to address that. The life cycle of HBV was analyzed by the ectopic expression of ISG20 in HepG2 and HepG2‐NTCP cells. Finally, to provide physiological relevance of our study, the expression of ISG20 from chronic hepatitis B patients was examined. RESULTS: Interferon‐stimulated gene 20 was mainly induced by interferon‐β and dramatically inhibited HBV replication. In addition, ISG20 decreased HBV gene expression and transcription. Although ISG20 inhibited HBV replication by reducing viral enhancer activity, the expression of transcription factors that bind the HBV enhancer was not affected. Particularly, ISG20 suppressed HBV enhancer activity by binding to the enhancer II and core promoter (EnhII/Cp) region. CONCLUSION: Our findings suggest that ISG20 exerts the anti‐HBV activity by acting as a putative repressor binding to the HBV EnhII/Cp region.